Factors affecting SME’s business success: a case study on young entrepreneurs / Nur Fatihah Malik - Malik, Nur Fatihah (Faculty of Business and Management, 2019)
The purpose of this research is to identify the factors affecting business success: A case study of young entrepreneurs. This study was conducted to know the relationship between independent (Entrepreneurial Competency, Marketing Capability, Technology Usage and Financial Resources) variable and dependent variable where it is correlated with each other. Hence with the proper observation, its aim study aims to investigate the factors affecting business success: A case study of young entrepreneurs. The first objective is to examine the relationship between entrepreneurial competency and determinants towards SMEs business success among young entrepreneurs. Secondly, to examine the relationship between marketing capabilities and determinant towards SMEs business success among young entrepreneurs. Thirdly, to examine the relationship between financial resources and determinant towards SMEs business success among young entrepreneurs. Lastly, it was to examine the relationship between technology usage and determinant towards SMEs business success among young entrepreneurs The sampling design that used in this research is non- probability sampling which is the judgemental sampling. The data collection method are primary data and secondary data which the primary data are conducted by distributed a questionnaire to the sample size where 102 of respondent which is the young entrepreneurs. The finding and research were result in frequency, descriptive, correlation and regression. Finally, the data, conclusions and recommendations are conducted.